Mediating role of fatigue driving in the influence of job demand and insecurity on safety incidents among bus drivers - Mustapha Amoadu; Isaac Tetteh Commey; Edward Wilson Ansah (Discover Psychology)
Abstract Background In developing countries, driving long-distance buses presents substantial road-traffic challenges. These are intensified by demanding job conditions and job insecurity, potentially leading to increased safety incidents linked to driver fatigue. This study sought to investigate how driving fatigue mediates the relationship between job demands, job security, and safety incidents among long-distance bus drivers in Ghana. Methods This survey sampled 7315 long-distance commercial bus drivers using a convenient sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. Findings Both job demands and job security showed significant positive associations with safety incidents among the drivers. Driving fatigue produced a partial mediation effect of job demands and job security on safety incidents of the drivers. This highlights crucial link between job stressors and driving performance. Conclusion The study indicates critical impact of job demands and job security on driving fatigue and subsequent safety incidents among bus these drivers in Ghana. Thus, addressing these stressors through targeted interventions, such as improved working conditions and fatigue management programmes, become essential for enhancing driver well-being and road safety in Ghana. Importantly, addressing these challenges requires collaborative efforts among transport authorities, policymakers, and other industry stakeholders to enforce regulations and promote supportive work environments for the drivers.